CULTURA MAKER NA EDUCAÇÃO: O ENSINO DA ROBÓTICA PARA A FORMAÇÃO DOCENTE INICIAL - Santos, Raiayne Souza (2021)
This dissertation research is inserted in the Education, Culture and Diversity’s field of studies of the Graduate Program in Education, at Universidade Estadual do Centro-Oeste. It also joins the Laboratory of Communication, Education and Technology Studies, in which the Study Groups in Distance Education and Digital Technologies and in Education, Technology and Culture belong to. This study starts from the importance of training future teaching professionals who understand and relearn pedagogical proposals. Thus, the following question is problematized: how to use pedagogical practices on maker culture, in particular, the teaching of robotics in the teaching practices? Therefore, the main aim of this research is to investigate the maker culture and robotics teaching for using it in the teaching practices. For that, this work has the following specific objectives: a) research on initial teacher training and the using of technologies in education; b) contextualize the education and maker culture; c) study about education and robotics as a resource in teaching practices and d) to develop an online course on maker culture in education, as well as its potential in initial teacher training. The methodological procedure was carried out through bibliographical and empirical research from the application of an online course for teachers in initial training on "Maker Culture in Education: robotics with arduino" for Pedagogy graduation students at UNICENTRO in 2020 academic year, through the Virtual Learning Environment, also known as Moodle. It’s development consisted in forty-eight hours. The data collection instruments were: an initial semi-structured questionnaire and a final semi structured one, both available through the digital platform Google Forms. The authors who supported this study were: Mochon and Salazar (2003), Moran (2000), Raabe and Gomes (2018) and others. Based in this research, it is considered that the maker culture with a focus on educational robotics can become an instigating proposal for pedagogical practices of future teachers. However, there is a concern about content planning, because the future teachers must also work in accordance to the structure condition of the school environment that they will work. For example: observing if it has internet or not. In addition, it is up to the school management to analyze if the teaching of robotics will be curricular or extracurricular depending on an adaptation.